Reframing English Curriculum Policy: A Comparative Analysis between Indonesia and the United States for Local Instructional Design - Hilwa Waniza; Ira Maisarah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This article aims to compare the secondary school English curriculum in Indonesia and the United States to identify differences in curriculum orientation, instructional design, and assessment practices. Using a Systematic Literature Review (SLR) approach, ten academic articles and official curriculum documents published between 2020 and 2025 were examined. The findings show that Indonesia’s curriculum remains centralized and exam-oriented, which limits teacher autonomy and reduces opportunities for authentic, student-centered learning. Meanwhile, the U.S. curriculum emphasizes flexibility, critical thinking, formative assessment, and multicultural integration, allowing greater adaptation to students’ needs. Based on this comparison, the study concludes that curriculum development in Indonesia requires selective adaptation of key elements such as teacher empowerment, localized flexibility, performance-based assessment, and balanced cultural representation. The article contributes to curriculum discourse by offering a comparative perspective that can inform policymakers and English educators in designing a more adaptive and competence-based English curriculum for secondary education. Keywords: English Curriculum; Comparative Education; Curriculum Design; Instructional Policy; Curriculum Development